Counselling Issues with International Students - Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
As Canadian post-secondary institutions increase their marketing and recruitment efforts to attract international students, attention must also be paid to comprehensive support services. A supportive campus environment is essential for assisting international students to attain their academic and personal goals. Counsellors have an integral role in the delivery of direct counselling and campus outreach programming to international students. Issues faced by international students in the transition to living and learning in Canada are reviewed with specific suggestions for counsellors to address the adjustment concerns of international learners.